Охорона здоров’я дітей і організація санітарно-гігієнічного контролю у шкільництві Волинського воєводства (1921–1939 рр.) - Валентина Доброчинська; Наталія Переходько (Scientific Papers of the Vinnytsia Mykhailo Kotsyiubynskyi State Pedagogical University Series History, 2026)
The purpose of the article is to analyze the historical experience of organizing sanitary and hygienic control in the school system of the Volhynian Voivodeship in interwar Poland and to determine the directions of state policy aimed at implementing medical-preventive and health-promoting measures in education; to elucidate the features of cooperation between the pedagogical and medical communities to create favorable learning conditions and to preserve and improve children’s health. Methodology. The research methodology relies on the comprehensive application of general scientific methods—analysis, synthesis, objectivity, and historicism—as well as specialized historical methods: historical source analysis, historical-comparative, historical-genetic, and historical-systemic approaches. Scientific novelty. The scientific novelty lies in providing the first comprehensive study and analysis of sanitary and hygienic control, medical supervision, and preventive measures against infectious diseases in the school system of the Volhynian Voivodeship. The joint initiatives of two sectoral ministries—the Ministry of Religious Denominations and Public Education and the Ministry of Public Health—in addressing the health protection of schoolchildren are revealed. The sanitary-hygienic and medical-preventive requirements for the optimal organization of the educational process in interwar schools are substantiated. Conclusions. It has been established that specialized healthcare institutions of the Second Polish Republic collaborated with the Ministry of Religious Denominations and Public Education to raise a healthy young generation under the difficult conditions of the post-war period, responding to severe epidemiological challenges. On the one hand, the study highlights the efficiency and professionalism of Polish officials who implemented a range of measures to structure the educational process in accordance with sanitary-hygienic and child health standards. On the other hand, the practical implementation of these regulatory provisions in the Volhynian Voivodeship faced significant obstacles, such as a low level of sanitary-hygienic culture among the population, financial constraints of local authorities, and a shortage of qualified medical personnel both in schools and in the region as a whole. Nevertheless, systematic medical-preventive measures during the interwar period, combined with the efforts of public organizations, contributed to improving sanitary and hygienic conditions in schools and fostering a culture of health among schoolchildren.